Studi Analisis Rasi Bintang Orion Sebagai Acuan Penentu Arah Kiblat di Malam Hari Perspektif Astronomi - Sulnanda; Rahmatiah,HL; Chotban, Sippah (HISABUNA: Jurnal Ilmu Falak, 2024)
Qibla direction is the direction in which Muslims worship. The sun, stars and other celestial bodies have been used by human civilizations as clues to establish their position for several centuries, and are closely related to the implementation of worship. As an illuminator and decorator of the sky there are constellations that are used as a reference at night. Because at night the constellations can be used as directions. The constellation Orion serves as a guide for fishermen and all mankind because it is too young to be seen with the naked eye with its position pointing west. This type of research uses library research "Library Research" refers to this type of research, which describes the subject matter accurately, systematically, and normatively to the object. The data sources used are primary data and secondary data, Primary Data in this study are data obtained directly from the research topic to be examined or data collection tools that are directly used as topics, which are the source of the information sought. Secondary data in this study is a source of information that supports this research, From the results of this study obtained that 1. Identification of the Orion Constellation as a reference for determining the Qibla direction at night. 2. The accuracy of the Orion Constellation as a reference for determining the Qibla direction at night. Qibla direction at night can be determined by referring to the constellation of Orion. By using one of its stars, Rigel, as a benchmark for determining the Qibla direction, namely by knowing the azimuth of the star, which can be observed using the stellarium application, or by using data and formulas to determine the Qibla direction using the azimuth of the Rigel star. The results after three comparisons, there is only a difference of one minute and one second between the azimuth of the Sun and Rigel star, according to calculations, this indicates that Rigel star is accurate as a reference for determining the Qibla direction at night. The implication of this research is that the use of Rigel star in the Orion constellation in this study is used as an alternative to determine the Qibla direction at night.